“BAM”: a collaborative R&D project for the development of a simulation based solution for the design and manufacture of 3D woven composites - Said, Rajab; Müller, Sebastian; de Luca, Patrick; Thompson, Adam; El Said, Bassam; Hallett, Stephen; Endruweit, Andreas; Brown, Louise; Long, Andrew; Koncherry, Vivek; Potluri, Prasad (2017)
Breakthrough Aerospace Materials (BAM) is a collaborative R&D project based in the UK [1]; led by industry and co-funded by the British Government via the Innovate-UK under its Aerospace Technology Institute (ATI) R&T Programme. The overall objective of BAM is to develop a complete process that will enable aerospace industry (and others) to design and manufacture complex shaped components using 3D woven composites. This material offers great advantages particularly for producing lightweight structures with high resistance to impact loading and damage - yet, there is still no evidence of it been widely adopted by industry! It is agreed that one of the major reasons behind slow adoption of the 3D woven composites by industry is the lack of industrial simulation tools that can be used effectively by design and analysis engineers. A consortium consisting of 12 partners, involving 9 from industry and 3 from academia, was set up to work towards this goal over a period of three years. As it is less than a year since the kick-off of the project, this paper will mainly introduce the general approach for now - leaving the full demonstration of applying the developed technologies on industrial cases for follow up publications. However, a few independent illustration examples are still presented - while elaborating on the current status of development at various steps in the process and its associated challenges. The paper also aims to highlight the interdependence between industrial and academic partners for their success in pushing the required technology up the TRL (Technology Readiness Level) scale. Two leading CAE software developers (ESI Group and MSC Software) are involved in BAM, and both are working on developing their own strategy to tackle the problem. The paper will elaborate on the approach adopted by ESI in particular, which is aligned with its global strategy for providing virtual end-to-end solution for composites product development.